2017
DOI: 10.7897/2230-8407.086101
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Phenolic Compounds and Antioxidant Potential of Crude Extract and Fractions of Mimosa Hamata

Abstract: The present study aimed to evaluate the phenolic compounds and in vitro antioxidant properties of ethanolic extract and selected fraction of Mimosa hamata whole plant. Phytochemical analysis of the extract of M. hamata indicated the presence of phenols and flavonoids in plant. The highest total phenolic and flavonoid content was observed in the IG fraction of M. hamata (654.33 ± 0.008 mg/g and 689.66 ± 0.032 mg/g respectively) in comparison to other fractions. The present investigation showed that ethanolic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Phytochemical studies of this genus revealed the presence of flavonoids, steroids, saponins, alkaloids, coumarins, tannins [ 24 , 25 ] and terpenoids [ 26 ]. The genus Mimosa showed several pharmacological activities, such as antiseptic, antimicrobial [ 27 , 28 ], antidiabetic [ 29 , 30 ], antihistamic [ 31 ], antioxidants [ 32 , 33 , 34 , 35 , 36 , 37 ], anticonvulsant [ 38 ], antigout [ 39 ], antispasmolytic [ 40 ], anti-inflammatory [ 41 , 42 , 43 ], antinociceptive [ 44 , 45 ], antiulcer [ 43 ], antifertility [ 46 ], antimalarial [ 47 ], antiparasitic [ 48 ], wound healing [ 49 ], anticancer [ 50 , 51 ], antidepressant [ 52 ], antidiarrheal [ 53 , 54 ], hypolipidemic [ 55 , 56 ], hepatoprotective [ 57 ], antivenom [ 43 ], antiproliferative [ 58 ], antiviral [ 59 ] and aphrodisiac [ 60 ]. Previously our group efficiently documented the indigenous flora of Pakistan and also a few exotic species [ 61 , 62 , 63 , 64 , 65 , 66 ...…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical studies of this genus revealed the presence of flavonoids, steroids, saponins, alkaloids, coumarins, tannins [ 24 , 25 ] and terpenoids [ 26 ]. The genus Mimosa showed several pharmacological activities, such as antiseptic, antimicrobial [ 27 , 28 ], antidiabetic [ 29 , 30 ], antihistamic [ 31 ], antioxidants [ 32 , 33 , 34 , 35 , 36 , 37 ], anticonvulsant [ 38 ], antigout [ 39 ], antispasmolytic [ 40 ], anti-inflammatory [ 41 , 42 , 43 ], antinociceptive [ 44 , 45 ], antiulcer [ 43 ], antifertility [ 46 ], antimalarial [ 47 ], antiparasitic [ 48 ], wound healing [ 49 ], anticancer [ 50 , 51 ], antidepressant [ 52 ], antidiarrheal [ 53 , 54 ], hypolipidemic [ 55 , 56 ], hepatoprotective [ 57 ], antivenom [ 43 ], antiproliferative [ 58 ], antiviral [ 59 ] and aphrodisiac [ 60 ]. Previously our group efficiently documented the indigenous flora of Pakistan and also a few exotic species [ 61 , 62 , 63 , 64 , 65 , 66 ...…”
Section: Introductionmentioning
confidence: 99%
“…Anthraquinone, alkaloids, catechol, flavonoids, and phenolic acids are among examples. saponins, steroids, tannins, and triterpenoids are all examples of chemicals respectively [4]. Natural medicines are currently in demand, and their popularity is growing.…”
Section: And Researcher's Preliminary Phytochemical Quality Assessmentmentioning
confidence: 99%